Antipsychotic-like activity of Noni (Morinda citrifolia Linn.) in mice - Pandy, V.; Narasingam, M.; Mohamed, Z. (2012)
Background: Noni fruit is widely consumed in tropical regions of Indonesia to the Hawaiian Islands. The noni plant has a long history of use as a medicinal plant to treat a wide variety of ailments including CNS disorders. The present investigation was designed to evaluate the antipsychotic effect of noni fruits (Morinda citrifolia Linn.) using mouse models of apomorphine-induced climbing behaviour and methamphetamine-induced stereotypy (licking, biting, gnawing and sniffing).Methods: In acute study, the methanolic extract of Morinda citrifolia (MMC) at different doses 1, 3, 5, 10 g/kg was administered orally one hour prior to apomorphine (5 mg/kg, i.p) and methamphetamine ( 5 mg/kg, i.p) injection respectively in Swiss albino mice. In chronic studies, (TAHITIAN NONIÂ® Juice, TNJ) was made available freely in daily drinking water at 30, 50 and 100 v/v for 7 days; 30 and 50 v/v for 21 days respectively. On the test day, an equivalent average daily divided dose of TNJ was administered by oral gavage one hour prior to apomorphine treatment. Immediately after apomorphine/ methamphetamine administration, the animals were placed in the cylindrical metal cages and observed for climbing behaviour/ stereotypy and climbing time.Results: The acute treatment of MMC (1, 3, 5, 10 g/kg, p.o) significantly decreased the apomorphine-induced cage climbing behaviour and climbing time in mice in a dose dependent manner. The MMC also significantly inhibited methamphetamine-induced stereotypy behaviour and climbing time in mice dose-dependently. The 7 and 21 days treatment of TNJ in drinking water at 50 and 100v/v significantly alleviated the apomorphine-induced climbing behaviour and climbing time in mice.Conclusions: The present study results demonstrated the antidopaminergic effect of Morinda citrifolia Linn. in mice, suggesting that noni has antipsychotic-like activity which can be utilized in the treatment of psychiatric disorders. However further studies are warranted to identify the active principles responsible for the antipsychotic activity of noni. Â© 2012 Pandy et al.; licensee BioMed Central Ltd.